Chinese Funding: A Curse to Africa - Chido T Chipfakacha (African Journal of Political Science)
The role of China in the liberation of Africa from colonial rule cannot be down played as I laid a foundation to Africa today. Most African countries were aided by China militarily and ideologically in the fight against Western colonial rule. Though some scholars would suggest that China`s contribution was as a result of the hostility that was there in the times of the cold war between the self-acclaimed democrats of the Western bloc and the Communist Eastern bloc. Philosophers like Marx Engel, Karl Marx, Lenin and Mao Zedong had a major influence on the liberation of Africa. The purpose of this paper is to show how the relationship that started as sincere has become a curse for the poor and unconnected Africans. In recent years the Chinese has overtaken the Briton hood Institutes of the International Monetary Fund (IMF) and World Bank as the major lenders of loans to African States.  Kwame Nkrumah warned us of the danger of Africa being recolonised in what he termed neo colonialism where the colonisers will come as investors. Neo colonialism is no longer a theory but has become a reality as will be exposed in this article using empirical, qualitative and quantitative research methods to show how  a friendship with China has benefited the elite politicians at the cost of citizens affairs. Africa is endowed with natural resources yet it has the poorest population per Gross Domestic Product (GDP) per capita. The paper will show how it is easy for a Chinese to own a business in Africa compared to the native Africans using the case of Shurugwi in Zimbabwe.